N‐3 PUFA deficiency disrupts oligodendrocyte maturation and myelin integrity during brain development. Issue 1 (14th September 2021) - Leyrolle, Quentin; Decoeur, Fanny; Dejean, Cyril; Brière, Galadriel; Leon, Stephane; Bakoyiannis, Ioannis; Baroux, Emilie; Sterley, Tony‐Lee; Bosch‐Bouju, Clémentine; Morel, Lydie; Amadieu, Camille; Lecours, Cynthia; et al.
Abstract: Westernization of dietary habits has led to a progressive reduction in dietary intake of n‐3 polyunsaturated fatty acids (n‐3 PUFAs). Low maternal intake of n‐3 PUFAs has been linked to neurodevelopmental disorders, conditions in which myelination processes are abnormal, leading to defects in brain functional connectivity. Only little is known about the role of n‐3 PUFAs in oligodendrocyte physiology and white matter development. Here, we show that lifelong n‐3 PUFA deficiency disrupts oligodendrocytes maturation and myelination processes during the postnatal period in mice. This has long‐term deleterious consequences on white matter organization and hippocampus‐prefrontal functional connectivity in adults, associated with cognitive and emotional disorders. Promoting developmental myelination with clemastine, a first‐generation histamine antagonist and enhancer of oligodendrocyte precursor cell differentiation, rescues memory deficits in n‐3 PUFA deficient animals. Our findings identify a novel mechanism through which n‐3 PUFA deficiency alters brain functions by disrupting oligodendrocyte maturation and brain myelination during the neurodevelopmental period. Main Points: Low n‐3 PUFA affects oligodendrocyte maturation and myelin integrity in juveniles. Low n‐3 PUFA has long‐term consequences on brain structure and function. Clemastine, which promotes oligodendrocyte maturation, rescues memory deficits in juveniles.